Decreasing frequency and extent of frost damage in European oaks over 1961-2021 - Jianhong Lin; Nicolas Delpierre; Fabien Caroulle; Sebastien Cecchini; Vincent Badeau; Thomas Caignard; Daniel Berveiller; Sylvain Delzon; Heikki Hänninen; Antoine Kremer; Annette Menzel; Alexandre Morfin; et al. (Agricultural and Forest Meteorology, 2026)

Plot level nitrogen stock is enhanced by a young agroforestry system in a mediterranean environment - Mubarak Mahmud; Isabelle Bertrand; Jerôme Ngao; Soline Martin-Blangy; Stéphane Bazot; Nicolas Delpierre; Paul Leadley; Gaëlle Vincent; Claire Marsden; Rémi Dugue; Alexandre Morfin; Marion Forest; et al. (Agroforestry Systems, 2025)
A 2-years assessment of nitrogen (N) stocks, tree N safety nets (from a 15 N labeling experiment), and biological N fixation was conducted in a Mediterranean agroforestry system in southern France. The study aimed to quantify N retention in agroforestry. The study area is characterized by a skeletic rhodic luvisol soil, a mean annual temperature of 15.5 °C, and an average annual precipitation of 556 mm. N and 15 N were quantified across all system components, which are N-fixing black locust trees, crops, weed plants, understory vegetation strips (UVS), rhizospheric soil, and soil microbial biomass. A split-plot experimental design was used, with agroforestry (AF) and monoculture (MC) plots. 15 N labeling was applied to track N fluxes and determine tree nutrient absorption over time. We hypothesized that tree root growth and nutrient leaching would enhance the safety-net effect, improving N retention. Results showed that crops in AF had lower N stocks (13–30% less than MC), but tree and UVS contributions compensated for the deficit, leading to a 62% increase in total plot-level N stock in 2022. The Relative Nitrogen Content was 0.97 in 2021 and 1.63 in 2022. While no 15 N was detected in trees in the first year (70 days after labeling), 2% of applied 15 N was recovered in trees 14 months post-labeling. % of N derived from atmospheric N 2 (%Ndfa) ranged from 52 to 68%, with trees fixing 14–18 kg N ha −1 . We confirmed that agroforestry enhances N retention, but further research is needed to quantify leaching and gaseous losses of nitrogen.

Phenology Across Scales: An Intercontinental Analysis of Leaf‐Out Dates in Temperate Deciduous Tree Communities - Nicolas Delpierre; Suzon Garnier; Hugo Treuil‐Dussouet; Koen Hufkens; Jianhong Lin; Colin Beier; Michael Bell; Daniel Berveiller; Matthias Cuntz; Giulio Curioni; Kyla Dahlin; Sander O. Denham; et al. (Global Ecology and Biogeography, 2024)
Aim To quantify the intra‐community variability of leaf‐out (ICVLo) among dominant trees in temperate deciduous forests, assess its links with specific and phylogenetic diversity, identify its environmental drivers and deduce its ecological consequences with regard to radiation received and exposure to late frost. Location Eastern North America (ENA) and Europe (EUR). Time Period 2009–2022. Major Taxa Studied Temperate deciduous forest trees. Methods We developed an approach to quantify ICVLo through the analysis of RGB images taken from phenological cameras. We related ICVLo to species richness, phylogenetic diversity and environmental conditions. We quantified the intra‐community variability of the amount of radiation received and of exposure to late frost. Results Leaf‐out occurred over a longer time interval in ENA than in EUR. The sensitivity of leaf‐out to temperature was identical in both regions (−3.4 days per °C). The distributions of ICVLo were similar in EUR and ENA forests, despite the latter being more species‐rich and phylogenetically diverse. In both regions, cooler conditions and an earlier occurrence of leaf‐out resulted in higher ICVLo. ICVLo resulted in ca. 8% difference of radiation received from leaf‐out to September among individual trees. Forest communities in ENA had shorter safety margins as regards the exposure to late frosts, and were actually more frequently exposed to late frosts. Main Conclusions We conducted the first intercontinental analysis of the variability of leaf‐out at the scale of tree communities. North American and European forests showed similar ICVLo, in spite of their differences in terms of species richness and phylogenetic diversity, highlighting the relevance of environmental controls on ICVLo. We quantified two ecological implications of ICVLo (difference in terms of radiation received and exposure to late frost), which should be explored in the context of ongoing climate change, which affects trees differently according to their phenological niche.

Assessing Nutrient Safety Net and Crop Yield in a Mediterranean Agroforestry Using 15N Labelling Experiment - Mubarak Mahmud; Isabelle Bertrand; Stéphane Bazot; Nicolas Delpierre; Paul Leadley; Jerôme Ngao; Claire Marsden; Rémi Dugue; Alexandre Morfin; Anne Marmagne; Laure Barthes (Journal of Soil Science and Plant Nutrition, 2024)

Associating a negatively charged GdDOTA-derivative to the Pittsburgh compound B for targeting Aβ amyloid aggregates - André F. Martins; Alexandre C. Oliveira; Jean-François Morfin; Douglas V. Laurents; Éva Tóth; Carlos F. G. C. Geraldes (JBIC Journal of Biological Inorganic Chemistry, 2016)